Desenvolvimento e avaliação físico-química e microbiológica de cosméticos para a pele humana contendo óleos de Macaúba (Acrocomia aculeata (Jacq.) Lodd. ex Mart.) - Fabricio Costa Callegari (2015)
This work aimed to evaluate the potential application of Macauba (Acrocomia aculeata (Jacq. Lodd. ex Mart.) pulp and kernel oils for cosmetic purposes, in order to build value to the marketing of the oils, and indirectly, contribute to the strengthening of Macaúba culture, as a new sector for Brazilian agribusiness currently underway, mainly in Minas Gerais State. Oleic and palmitic fatty acids are predominant in the pulp oil, and in the kernel oil, lauric and oleic fatty acids can be detected. All these components are similar to natural moisturizing ingredients present in the epidermis, which allows following the cosmetic trend of biomimetic products. Furthermore, the presence of significant amounts of carotenoids, tocopherols and phenolic compounds in the pulp and kernel oils suggests the pharmacological properties of these naturally occurring compounds. In this research, Macauba palm fruits collected in the Pampulha campus of the Federal University of Minas Gerais were processed in order to extract the pulp and kernel oils by mechanical pressing. From both oils, O/W emulsions containing 10% (w/w) of these oils were developed using non-ionic surfactants classically employed in the cosmetics industry. Four formulations were prepared, two with the characteristic of being highly viscous creams, and the other two having lower viscosity, the lotions. Preliminary stability tests indicated the formulations with satisfactory performance in the categories stability and appropriate apparent viscosity. Preliminary stability testing, accelerated stability study, rheological profile and the preservative challenge test were used as evaluation criteria. Macroscopic characteristics (appearance, color and odor) and obtained density, pH and conductivity during the evaluation, suggested the stability of the formulations. Keywords: macauba oil; Acrocomia aculeata; cosmetic emulsions; stability; rheological profile; challenge test.